Double Transplanting of Boro Rice Increased System Productivity of T. Aman-Potato-Boro Cropping Pattern (The Agriculturists, 2010)
Under irrigated condition, double transplanting (DT) of Boro rice in a T. Aman-Potato-Boro cropping pattern may be an alternative option either to reduce the yield loss of late planted Boro rice or to keep it at a minimum level. An experiment was conducted during 2003 - 2006 at Gazipur and Kapasia with three cropping patterns. The patterns were: T. Aman- Boro- Fallow (CP1), T. Aman-Potato- Boro (CP2) and T. Aman- Potato- double transplanted (DT) Boro (CP3). Rice varieties were BRRI dhan44 and BRRI dhan29 for Aman and Boro seasons, respectively; while Diamont was the potato variety. Rice equivalent yields (REY) in CP2 and CP3 were 82 and 109% higher than that in CP1 at Gazipur, whereas those were 122 and 179% higher at Kapasia. The increase of REY in CP2 was attributed to higher potato yield and that in CP3 was due to higher yield of potato and Boro rice. Double transplanting of Boro in CP3 facilitated greater yield of potato and realized almost similar yield of Boro that was obtained in CP1. Economic analysis showed that the gross margin was the highest in CP3 (US$ 1797 and 2720 at Gazipur and Kapasia, respectively). CP3 may be recommended for medium high lands of Bangladesh and other Asian rice growing countries.